"A life-changing experience and the beginning of a lifelong commitment": experiences and impact of Global Health Community Service-Learning in undergraduate dental curriculum in Canada - Abbas Jessani; Alexia Athanasakos; Samantha Kachwinya (BMC, 2024)
Abstract Background Global Health Community Service-Learning (GHCSL) can have a profound professional and personal impact on learners. This pedagogy provides understanding of unfamiliar environments and challenges learners to step out of their comfort zones, adapt to new cultures, and navigate unique situations. Yet, there are relatively few studies exploring the experiences of learners participating in community service-learning placements in global regions as part of undergraduate dental curriculum. This study aimed to explore the experiences and impact of the GHCSL program in East Africa among undergraduate dental learners at the Schulich School of Dentistry. Methods Eight undergraduate dental learners were enrolled in GHCSL pilot placements. Placement agreements were established with Makerere University in Kampala, Uganda, and the University of Rwanda in Kigali, Rwanda for the summer of 2022. Stakeholders from both institutions were engaged in the development and implementation of these placements. Learners were required to engage in weekly reflection through a 'storytelling and incident-based narrative' while carrying out their placement. A qualitative study design was employed, and an inductive interpretive approach was utilized to thematically analyze the learners' reflective essays. Results Five major themes emerged from the learners' reflective essays: (1) experiential clinical learning; (2) cultural humility and social awareness; (3) awareness of contrasting healthcare systems; (4) commitment to service; and (5) personal and professional growth. Most learners reflected on their engagement with diverse communities, being exposed to unique patient cases, and witnessing the adaptability exuded in resource-constrained environments. These experiences presented the learners with an opportunity to develop cultural humility and gain a newfound motivation to mitigate global oral health disparities in populations beyond that of their local communities. Learners also reflected on enhanced social awareness experiences and the awareness of contrasting healthcare systems in Canada and their placements, which encouraged the development of empathy, communication, and compassion skills, as well as an understanding of the disproportionate burden of conditions in low-resource settings. Conclusion The reflective essays concluded that the GHCSL placements had a positive impact on the learners, encouraging many to develop a heightened desire for lifelong learning to address oral health disparities within a global context.